Kangaroo position in low birth weight preterm newborns: descriptive study - Samilly Rodrigues Farias; Flávia de Souza Barbosa Dias; Juliana Bastoni da Silva; Ana Lidia de Lucca Ribeiro Cellere; Lidia Beraldo; Elenice Valentim Carmona (Universidade Federal de Goias, 2017)
To describe the number of periods that very low birth weight preterm newborns were in kangaroo position during admission in the neonatal unit and to look for relations between maternal and neonatal variables with kangaroo position. A retrospective and descriptive study with all preterm newborns admitted in 2012, weighing 1500g or less and, gestational age lower than 31 weeks, classified as high clinical risk patients according to the Clinical Risk Index for Babies. We identified 38 babies whose admittance time ranged from 18 to 136 days. The beginning of kangaroo position occurred on average at 30.8 days of post-natal life (SD=18.5) and the number of periods in kangaroo position was on average 10.7 times. The occurrence of kangaroo position was less frequent than opportunities from the maternal presence, and the position was related to a higher offering of free milk demand.